Deleveraging after Lehman : evidence from reduced rehypothecation - Singh, Manmohan, 1964-; Aitken, James (IMF working paper, 2009)
Rehypothecation is the practice that allows collateral posted by, say, a hedge fund to their prime broker to be used again as collateral by that prime broker for its own funding. In the United Kingdom, such use of a customer's assets by a prime broker can be for an unlimited amount of the customer's assets. And moreover, there are no customer protection rules (such as in the United States under the Securities Act of 1933). The paper shows evidence that, following Lehman's bankruptcy, the extent of rehypothecation has declined substantially, in part because investment firms fear losing collater.